2015
DOI: 10.1371/journal.pmed.1001786
|View full text |Cite|
|
Sign up to set email alerts
|

Intra-tumor Genetic Heterogeneity and Mortality in Head and Neck Cancer: Analysis of Data from The Cancer Genome Atlas

Abstract: BackgroundAlthough the involvement of intra-tumor genetic heterogeneity in tumor progression, treatment resistance, and metastasis is established, genetic heterogeneity is seldom examined in clinical trials or practice. Many studies of heterogeneity have had prespecified markers for tumor subpopulations, limiting their generalizability, or have involved massive efforts such as separate analysis of hundreds of individual cells, limiting their clinical use. We recently developed a general measure of intra-tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
255
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 252 publications
(264 citation statements)
references
References 45 publications
8
255
0
1
Order By: Relevance
“…Sequencing of different regions within a tumor reveals equally staggering intra-tumor genomic heterogeneity [13][14][15][16][17] , which is dynamic over time [18][19][20][21][22] . Taken together, these results are consistent with models of rapid genomic evolution within tumors and intra-tumoral genomic heterogeneity increasing over time, correlating with tumor aggressiveness and decreased patient survival [23,24] . Genomic instability can be initiated by exogenous or endogenous agents.…”
Section: Genomic Instability In Cancerssupporting
confidence: 84%
“…Sequencing of different regions within a tumor reveals equally staggering intra-tumor genomic heterogeneity [13][14][15][16][17] , which is dynamic over time [18][19][20][21][22] . Taken together, these results are consistent with models of rapid genomic evolution within tumors and intra-tumoral genomic heterogeneity increasing over time, correlating with tumor aggressiveness and decreased patient survival [23,24] . Genomic instability can be initiated by exogenous or endogenous agents.…”
Section: Genomic Instability In Cancerssupporting
confidence: 84%
“…For similar reasons, known oncogenes might be potent CIN drivers because they moderately affect the expression and function of genes involved in genome maintenance. Nevertheless, CIN enables the exploration of a phenotypic landscape in a way that cannot be achieved with an increased mutation rate alone (Mroz et al 2015). A deep understanding of the underlying causes of CIN and the context enabling its propagation is still lacking and needs thorough longitudinal studies to fully understand its importance.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity denotes that tumors are composed of multiple clonal subpopulations of different characteristic cells, and thus, histological examination frequently reveals differences in cell morphology and properties, among cells in the same cancer specimen [20]. Enhanced intra-tumor heterogeneity was directly correlated with increased mortality; in particular, high heterogeneity and p53 mutation positivity were associated with higher mortality rates in a large cohort study of head and neck cancer [19]. In the present study, serial sections of tumor specimens frequently revealed the coexpression of NANOG, mutant p53, and CD44, which was associated with poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%